Kompetensi Manajerial Kepala SMP Al-Azhar 3 Way Halim Bandar Lampung - Amrulloh, Muhammad Afif; Istiyana, Emi (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2019)
ABSTRACTChanges in society and the multidimensional crisis that has long engulfed Indonesia have made it difficult to find the ideal leader who has a high commitment to his duties and responsibilities. In various fields of life, many leaders who are actually less qualified to carry out the mandate of leadership have resulted in a poor climate and school culture, and have even caused a lot of negative conflict and the stress of their subordinates. This study aims to describe the managerial competence of the principal in Al-Azhar Middle School 3 Way Halim Bandar Lampung, Bandar Lampung city. In focus, this study examines the principal managerial competencies of school planning, leading schools, and managing teachers and staff. This research is a qualitative study with a type of case study research. The research subject was the principal. The research data was collected through interviews, observation, and documentation. The results of this study are as follows: (1) the preparation of school planning is compiled every new school year by involving principals, teachers, staff, and Al-Azhar foundations that are used to support school progress, (2) in leading schools, principals always include the entire school environment, (3) management of teachers and staff under its auspices, principals always conduct evaluations every mid-school year and include teachers and staff in training and workshops to improve the quality of student learning so that the results are in accordance with the school's objectives .Keywords: Leadership, competence, managerial, planning  ABSTRAKPerubahan masyarakat dan krisis multidimensi yang telah lama melanda indonesia menyebabkan sulitnya menemukan sosok pemimpin ideal yang memiliki komitmen tinggi terhadap tugas dan tanggung jawabnya. Dalam berbagai bidang kehidupan banyak ditemui pimpinan-pimpinan yang sebenarnya kurang layak dalam mengemban amanah kepemimpinannya sehingga mengakibatkan buruknya iklim dan budaya sekolah, bahkan telah menimbulkan banyak konflik negatif dan setres para bawahan yang dipimpinnya. Penelitian ini bertujuan untuk mendeskripsikan kompetensi manajerial kepala sekolah di SMP Al-Azhar 3 Way Halim Bandar Lampung, kota Bandar Lampung. Secara fokus penelitian ini mengkaji kompetensi manajerial kepala sekolah terhadap perencanaan sekolah, memimpin sekolah, dan mengelola guru dan staf. Penelitian ini merupakan penelitian kualitatif dengan jenis penelitian studi kasus. Subjek penelitian adalah kepala sekolah. Data penelitian dikumpulkan melalui wawancara, observasi, dan dokumentasi. Hasil penelitian ini adalah sebagai berikut: (1) penyusunan perencanaan sekolah disusun setiap tahun ajaran baru dengan melibatkan kepala sekolah, guru, staf, dan yayasan Al-Azhar yang digunakan untuk menunjang kemajuan sekolah, (2) dalam memimpin sekolah, kepala sekolah selalu mengikutsertakan seluruh lingkungan sekolah, (3) pengelolaan guru dan staf yang berada dibawah naungannya, kepala sekolah selalu mengadakan evaluasi setiap pertengahan tahun ajaran dan mengikutsertakan guru beserta staf dalam pelatihan-pelatihan aupun workshop guna meningkatkan kualitas belajar mengajar peserta didik agar hasilnya maksimal sesuai dengan tujuan sekolah.Kata kunci: Kepemimpinan, kompetensi, manajerial, perencanaan